Behavioural drivers influencing emergency department attendance in Victoria during the 2020 COVID‐19 pandemic: A mixed methods investigation. (27th May 2022) - Buntine, Paul; Aldridge, Emogene S; Craig, Simon; Crellin, Dianne; Stella, Julian; Gill, Stephen D; Wright, Breanna; Mitchell, Rob D; Arendts, Glenn; Rawson, Helen; Rojek, Amanda M
Abstract: Objective: To identify behavioural drivers and barriers that may have contributed to changes in ED attendance during the first 10 months of the coronavirus disease 2019 (COVID‐19) pandemic in Victoria. Methods: We conducted a mixed methods analysis of patients who attended one of eight participating EDs between 1 November 2019 and 31 December 2020. A random sample of patients were chosen after their visit and invited to participate in an online survey assessing behavioural drivers and barriers to attendance. The study timespan was divided into four periods based on local and world events to assess changes in attitudes and behaviours over this period. Results: A total of 5600 patients were invited to complete the survey and 606 (11%) submitted sufficient information for analysis. There were significant differences in participants' attitudes towards healthcare and EDs, levels of concern about contracting and spreading COVID‐19 and the influence of mask wearing. Patients expressed more concern about the safety of an ED during the largest outbreak of COVID‐19 infections than they did pre‐COVID, but this difference was not sustained once community infection numbers dropped. General concerns about hospital attendance were higher after COVID than they were pre‐COVID. A total of 27% of patients specifically stated that they had delayed their ED attendance. Conclusion: Patients expressed increased concerns around attending ED during the first 10 months of the 2020 COVID‐19 pandemic and frequently cited COVID‐19 as a reason for delaying their presentation. These factors would be amenable to mitigation via focussed public health messaging. Abstract : A mixed methods study to identify behavioural drivers and barriers that may have contributed to changes in ED attendance during the first 10 months of the coronavirus disease 2019 (COVID‐19) pandemic in Victoria. Patients expressed increased concerns around attending ED during the first 10 months of the 2020 COVID‐19 pandemic and frequently cited COVID‐19 as a reason for delaying their presentation.